2021
DOI: 10.1039/d1bm00809a
|View full text |Cite
|
Sign up to set email alerts
|

Marine origin materials on biomaterials and advanced therapies to cartilage tissue engineering and regenerative medicine

Abstract: The body´s self-repair capacity is limited, including injuries on articular cartilage zones. Over the past few decades, tissue engineering and regenerative medicine (TERM) have focused the studies on the development...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 164 publications
0
14
0
Order By: Relevance
“…Recent study employed a mixture of hyaluronan hydrogel, which they then inserted under the skin of hairless rats. After multiple time points, the implant was subjected to histological, immunohistochemical, and mechanical analyses, compared to control studies, the implantation had good machinability, suggesting that cell and hydrogel mixtures could create like-cartilaginous tissue in vivo [ 25 ].…”
Section: Bioprinting Technologiesmentioning
confidence: 99%
“…Recent study employed a mixture of hyaluronan hydrogel, which they then inserted under the skin of hairless rats. After multiple time points, the implant was subjected to histological, immunohistochemical, and mechanical analyses, compared to control studies, the implantation had good machinability, suggesting that cell and hydrogel mixtures could create like-cartilaginous tissue in vivo [ 25 ].…”
Section: Bioprinting Technologiesmentioning
confidence: 99%
“…Furthermore, the scaffold should be conducive to the diffusion of nutrients, the discharge of metabolic waste, and should provide a stable external environment for cell growth and differentiation. In addition, the scaffold material should have good shapeability and it should be easy to prepare the tissue model of irregular defects ( Carvalho et al, 2021 ; Wei et al, 2021 ). Currently, sodium alginate and collagen are two of the most widely used hydrogels in cartilage tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, sodium alginate and collagen are two of the most widely used hydrogels in cartilage tissue engineering. When exposed to divalent cations, such as Ca 2+ , Ba 2+ or Sr 2+ , alginate generates a hydrogel that is similar to an extracellular matrix ( Ahmad Raus et al, 2021 ; Carvalho et al, 2021 ). Levato et al (2017) found that employing hydrogel as a bio-scaffold material could accelerate chondrogenesis and inhibit osteogenesis in CSPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Marine microorganisms, as important members of marine organisms, can produce numerous specific active substances in an extreme environment in low temperature, high salt, high pressure, and oligotrophic conditions. They have gained scientific interest due to their potential applications in the pharmaceutical, cosmetic and food industries, for environmental remediation, and astrobiology [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%